Efeito da eletronarcose e do método de insensibilização por atmosfera controlada no comportamento das aves ao abate, nos indicadores sanguíneos de estresse e nas características da carne - Pinto, Marcos Franke [UNESP]; Bitencourt, Diego Augusto [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Garcia-Neto, Manoel [UNESP]; Bossolani, Iderlipes Luiz Carvalho [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Brazil is the world’s largest exporter and third largest producer of chicken meat. To maintain competitiveness, the productive sector must always be alert to consumer demands, and concern about animal welfare is a growing tendency. Aspects involving animal welfare are especially critical in the slaughter of broiler chickens. This study evaluated the stunning of chickens in a CO2- enriched atmosphere chamber to reduce bird stress, comparing with electrical water bath stunning, the most usual desensitization method used in chicken slaughter. The reaction of birds when exposed to a high CO2 concentration (30%) and to a 10% initial CO2 level, gradually elevated to 30% was compared. The effect of mixing argon with CO2 was also evaluated, always aiming to reduce the discomfort of birds. In all the gas stunning parameters evaluated, evident discomfort reactions before stunning were observed in about two thirds of the birds, but the blood levels of corticosterone and glucose, used as stress indicators, indicated that gas increased the birds’ welfare. Gas exposure time required to stun the birds and time to regain consciousness after exiting the gas chamber presented a wide variation. Controlled atmosphere stunning method facilitated bird handling during slaughter, but more studies will be necessary to develop this technological alternative and make it viable for industrial use.
Effect of electrical and controlled atmosphere stunning methods on broiler chicken behavior at slaughter, blood stress indicators and meat traits
Keywords: Animal welfare; CO2; Human slaughter; Meat quality; Stress; Stunning